Antiproliferative and Antiviral Activity of Three Libraries of Adamantane Derivatives. Issue 5 (13th February 2014) - Basarić, Nikola; Sohora, Margareta; Cindro, Nikola; Mlinarić‐Majerski, Kata; De Clercq, Erik; Balzarini, Jan
<x xml:space="preserve">Abstract</x> Three libraries of adamantane derivatives were synthesized and evaluated for antiviral and antiproliferative activities against a broad variety of DNA and RNA viruses. Whereas none of the compounds exhibit antiviral activity at subtoxic concentrations, antiproliferative activity was found against murine leukemia cells (L1210), human T‐lymphocyte cells (CEM), and cervix carcinoma cells (HeLa) for 4, 8, and 10.